An examination of concussion education, management, and safety practices of girls' high school soccer coaches. Issue 3 (2nd September 2022) - Kim, Sungwon; Connaughton, Daniel P.; Sagas, Michael
ABSTRACT: The concussion rate in girls' soccer is among the highest in high school athletics. As such, coaches have a professional and ethical responsibility to reduce and properly manage concussions. The primary purpose of this study was to examine concussion education received, presence of athletic trainers, awareness of organizational concussion policy, concussion safety practices based on the presence of athletic trainers and coaches' demographic/professional background. Participants included 140 head coaches who voluntarily completed a survey. Results revealed the NFHS's Concussion in Sport (93.6%) was the most popular educational training received. Approximately 63% of coaches responded from schools where athletic trainers were present during all soccer games. A notable percentage of respondents did not know their high schools' concussion policy such as concussion education requirements (27.1%) and penalty from non-compliance (23.6%). This exploratory study informs stakeholders on the current status of concussion management policies and practices in high school girls' soccer.